Detection of Fish Freshness Using Immobilized ADP-ase and 5'-Nucleotidase on Polyacrylamide Gel - Djagal W Marseno; Retno Indrati; Sudarmanto Sudarmanto (Indonesian Association of Food Technologists, 1998)
The presence of ADP and IMP in the muscle of fish could be used as an indicator of its freshness. These metabolites could be detected enzymaticaly using ADPase and 51-nucleotidase. The aim of this research was to determine the presence of ADP and IMP in the muscle of fish qualitatively, using immobilized ADPase and 5'-nucleotidase on polyacrylamide gel. The results showed that in the non-immobilized form, ADPase has an optimum pH of 6 and stable at pH 5.5-10, while 5'-nucleotidase has two optima pH of 6.5 and 9 and it was stable at pH 7-10. Optimum temperature of ADPase and 5'-nucleotidase was 45 and 50°C, respectively. In the immobilized form, the activity of ADPase was optimum at pH 6 and it was still stable at pH 5.5 - 7.0 after storage at -20°Cfor 90 days, while 5'-nucleotidase was still stable at pH Z5-10 after storage at -20°C for 90 days. Both enzymes were more stable in frozen storage than that of chilled storage. Sensitivity of both enzymes to detect the fish freshness during storage was affected by the presence of free inorganic phosphate derived from other phosphate-containing metabolites.